Răspunsuri

Cel mai inteligent răspuns!
2014-03-10T20:25:53+02:00
Pai avem f(x)=g(x) si inlocuim -2x-1=5x+20 si -2x-5x=20+1⇒-7x=21/-7=x=-3 deci Gg intersectat cu Gf=A(-3,5) 
g(-3)=-3·5+20 =-15+20=5
multumesc mult!
Cu placere!
am facut bine: f(x)=5x-4 si g(x)=3x+14=>inlocuiesc 5x-4=3x+14 cu 5x-3x=4+14=>2x=18/ 2=x=9; g(9)=9 ori3+14=27+14=41 deci Gg intersectat cu Gf= A(9,41) ???
2014-03-10T21:35:39+02:00
F(x)=g(x) si inlocuim -2x-1=5x+20 si -2x-5x=20+1⇒-7x=21/-7=x=-3 deci Gg intersectat cu Gf=A(-3,5) 
g(-3)=-3·5+20 =-15+20=5
mersi mult! am facut bine: f(x)=5x-4 si g(x)=3x+14=>inlocuiesc 5x-4=3x+14 cu 5x-3x=4+14=>2x=18/ 2=x=9; g(9)=9 ori3+14=27+14=41 deci Gg intersectat cu Gf= A(9,41) ???